Castigat ridendo mores: história do Brasil e teatro francês na crônica de Machado de Assis - Callipo, Daniela Mantarro [UNESP] (My University, 2012)
The chronicles of Machado de Assis can be read as a historical document or a literary work. Characterized as a hybrid genre, the chronicle allows several readings and interpretations, but it’s always connected at the time and at the production’s context. The aim of this article is to averiguate how Machado de Assis commented the importants subjects of his time, mixing the french classic theater and the brazilian’s history.

As crônicas machadianas podem ser lidas como documento histórico e obra literária. Caracterizada como gênero híbrido, a crônica permite várias leituras e interpretações, mas está sempre atrelada a seu tempo, ao seu contexto de produção. Neste artigo, pretende-se analisar de que maneira Machado de Assis comentou os assuntos importantes de sua época, mesclando o teatro clássico francês e a História do Brasil.
Keywords: Chronicles of Machado de Assis; French theater; History; Crônica machadiana; Teatro francês; História